Earliest geometries: A cognitive investigation of Howiesons Poort engraved ostrich eggshells - Valentina Decembrini; Ludovica Ottaviano; Mattia Cartolano; Enza Elena Spinapolice; Silvia Ferrara (PLoS ONE, 2026)
This article presents the first quantitative geometric and spatial analysis of engraved ostrich eggshell (EOES) fragments from the Howiesons Poort (HP) technocomplex of the African late Middle Stone Age (MSA), to evaluate whether the EOES demonstrates genuine formal structuring and visuo-spatial organization. By considering their ‘non-accidental properties’—such as curvature, parallelism, and co-termination—which remain consistent across different viewpoints, as well as their metric properties, including angular inclinations, based on empirical thresholds, we show that the HP dataset systematically employs salient geometric features. These features are combined and embedded through complex cognitive operations, including the iteration and alignment of parallel lines, rotation of lines generating intersections with variable angular openings, and translation of specific elements nested within organized spatial layouts. These engravings therefore constitute an early material expression of complex graphic representation, attesting to a species-specific human capacity for organizing geometric thought. Overall, the patterns reflect a system of rules through which Homo sapiens in the HP organized visual forms, revealing the cognitive foundations of structured graphic behavior.